Removal of Nickel(II) from Aqueous Solution by Complexation-Ultrafiltration with Polyvinyl Pyrrolidone - Chen, Zhixin; Zeng, Jianxian; Ding, Yangen (Journal of Membrane and Separation Technology, 2016)
This study confers insight into the removal of Nickel(II) from aqueous solution by complexation-ultrafiltration (CP-UF) technique with water-soluble polymer polyvinyl pyrrolidone (PVP). The whole experiment process includes five parts: pre-treatment, CP-UF, concentration, decomplexation and regeneration of polymer. Numerous factors affecting the retention rate of Nickel(II) (RNi) and permeate flux (J), such as pH, loading ratio, transmembrane pressure (TMP), complexation time and added salt have been investigated. In the CP-UF process, RNi reaches nearly 94% while pH of 7, loading ratio of 4, TMP of 1.0 bar, temperature of 250C, complexation time of 30 min are chosen to be the optimal parameters. In the process of concentration, J declines slowly and RNi is very high at loading ratio of 4 and pH of 7. Nickel ion concentration in the retentate solution increases linearly with volume concentration factor. In the process of decomplexation, the decomplexation percentage of nickel(II)-PVP complex reaches 42%. The binding capacity of the regenerated PVP is close to that of fresh PVP, and the recovery percentage of binding capacity is higher than 90%.